The Effect of the Reduced Dose of GnRH on Conception, Ovulation and Ovarian Structures in Ovsynch Program of Lactating Dairy Cows - Karaca, Fikret; Dogruer, Gokhan; Saribay, Mustafa Kemal; Ergun, Yasar; Ates, Cafer Tayyar (Animal Review, 2017)
This study was conducted to evaluate the efficacy of reducing GnRH dose on the formation of ovulation and conception, and sizes of the ovarian structures following an Ovsynch program in lactating cows. The cows were allocated randomly to two treatment groups (full dose; FD, n=20 and half dose; HD, n=20). Cows in the FD group were treated with 10.5 µg buserelin acetate on day 0, with 0.150 mg D- cloprostenol 7 d later and with 10.5 µg buserelin acetate 2 d later. Estrous cycles in HD group were synchronized using the same scheme as FD-treated cows, but the dose of buserelin acetate was reduced to 5.25 µg at both GnRH administration times. Ovarian structures were monitored by ultrasound with a 6-8 MHz linear trans-rectal probe on days 0, 7, 9, 10, and 11. Cows were inseminated at the 16-20 h after second GnRH administration. No significant differences were observed in the dominant or ovulatory follicle diameters in FD and HD groups. Ovulation incidence from second GnRH injection by the 24 hour after fixed-time AI did not differ between FD (85 %) and HD (90 %) groups. Also, the conception percentages did not differ statistically between the HD (50%) and FD (40 %) groups.